2016
DOI: 10.1016/j.drugpo.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Blacks face higher risk of drug arrests in White neighborhoods

Abstract: Background Although Blacks and Whites in the United States use drugs at similar rates, Blacks are much more likely to be arrested for drug crimes. We tested the hypothesis that racial disparities in drug arrests are exacerbated in predominantly White neighborhoods. Methods Using publicly available data we calculated the disproportion of Black arrests as a function of the proportion of Black arrests over the proportion of Black residents within the 56 police service areas that make up the Washington, DC metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…In line with extant literature documenting higher implicit racial bias toward Latino/a (compared to White) adults among healthcare providers (Hall et al, 2015), the current study found greater implicit preference for punishment (vs. help) for Latino/a than for White PWIDs. These findings are also consistent with criminal justice statistics, indicating that racial/ethnic minority individuals are more likely to be arrested (Fielding-Miller et al, 2016; Mitchell and Caudy, 2015) and receive harsher sentences (Curry et al, 2008) than White persons for drug-related offenses.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with extant literature documenting higher implicit racial bias toward Latino/a (compared to White) adults among healthcare providers (Hall et al, 2015), the current study found greater implicit preference for punishment (vs. help) for Latino/a than for White PWIDs. These findings are also consistent with criminal justice statistics, indicating that racial/ethnic minority individuals are more likely to be arrested (Fielding-Miller et al, 2016; Mitchell and Caudy, 2015) and receive harsher sentences (Curry et al, 2008) than White persons for drug-related offenses.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, the greater proportion of individuals with SUDs, who are within the criminal justice versus healthcare system, is often cited as an example of discrimination following from addiction stigma (Bohnert et al, 2011; Degenhardt et al, 2014, 2011; Strathdee et al, 2015). Moreover, although rates of drug use and selling are comparable between racial/ethnic groups, minorities (compared to Whites) are significantly more likely to be arrested and receive harsher sentences for drug-related offenses (Curry et al, 2008; Fielding-Miller et al, 2016; Mitchell and Caudy, 2015). Also, compared to women, men are more likely to be sentenced and receive harsher sentences for drug-related crimes (Cano and Spohn, 2012; Davidson and Rosky, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…That is, bias toward substance-using persons may be sensitive to racial/ethnic and social class biases. These biases could help explain why racial and ethnic minorities are more likely to be arrested (Fielding-Miller et al, 2016) and receive harsher punishments for drug-related offenses (Curry and Corral-Camacho, 2008) than their white counterparts. Future work should explore this finding more carefully by examining the impact of social stigma, racial/ethnic biases, and class biases, on responses to drug-related offenders, both in the realm of official penal processing and related to providing care to overdose victims encountered by police officers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that disproportionate drug-related arrests of African Americans are strongly correlated with the percentage of white residents who live within a given neighborhood [31]. However, little empirical evidence exists on how a neighborhood's racial, gender, and SES composition may be associated with arrest disparities.…”
Section: Introductionmentioning
confidence: 99%
“…However, little empirical evidence exists on how a neighborhood's racial, gender, and SES composition may be associated with arrest disparities. Drawing on our previous analyses of drug-related arrests in Washington, DC [31], we conducted a crosssectional analysis using publicly available data to measure the intersection of race and gender at the neighborhood level as predictors of disproportionate drug-related arrest rates for African American men in Washington, DC, and tested the prediction that this association would be attenuated by neighborhood-level economic factors.…”
Section: Introductionmentioning
confidence: 99%